Theileria annulata Induced Secondary Hypoxia Causes Ischemic Myocarditis in Cattle Calves - Gupta, Kapil Kumar; Srivastava, Mukesh; Gupta, Neha (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Involvement of the myocardium in theileriosis is not a common phenomenon but is commonly ignored under field conditions due to lack of proper knowledge about the pathophysiology of the disease. In this study, the electrocardiographic (ECG) features and alteration in serum concentration of cardiac-specific biomarkers like cardiac troponin-I (cTnI) and creatinine kinase (CK-MB) were evaluated in healthy (n=10) and theileriosis affected (n=12) cattle calves. There were alterations in the ECG features and serum concentrations of cTnI and CK-MB in theileriosis-affected calves as compared to healthy ones. Electrocardiographic study in diseased animals revealed the presence of Sinus tachycardia, 1st degree AV block, Atrial premature complex, Left atrial hypertrophy, and Right atrial hypertrophy in 91.66%, 33.33%, 16.67, 50.00%, and 50.00% cases, respectively. Serum concentrations of cardiac troponin-I in healthy and diseased animals were 0.144±0.119 ng/mL and 1.271±0.342 ng/mL respectively, while serum concentrations of CK-MB in healthy and diseased animals were 34.039±2.983 ng/mL and 49.710±3.332 ng/mL, respectively. Results showed alteration in standard electrocardiographic features and change in normal serum concentration of cardiac biomarkers, both indicative of cardiac involvement in the clinical Theileria annulata infection